Balancing the supersaturation rate and coordination capability for upscaling high-performance perovskite photovoltaics - Peng, Wenjun; Wei, Jianan; Li, Hongbing; Feng, Wei; Liu, Mengting; Xu, Tianyang; Qiu, Shudi; Liu, Chong; Wagner, Michael; Distler, Andreas; Brabec, Christoph; Mai, Yaohua; et al. (Energy and Environmental Science, 2025)
Transferring the well-established perovskite ink formulations from antisolvent spin coating to scalable deposition techniques remains a great challenge, primarily owing to the strikingly different crystallization kinetics involved in the two processes. Here, we discover that a balanced trade-off between supersaturation rate and coordination capability plays an essential role in regulating the crystallization kinetics of the perovskite films deposited by scalable methods. In comparison with the commonly used DMF/DMSO solvent mixture, incorporating a small volume of NMP promotes rapid α-phase perovskite nucleation together with controllable crystal growth. Consequently, high-quality crystalline perovskite films with large grains and a void-free buried interface are readily obtained by blade coating. On these bases, inverted perovskite solar cells (0.09 cm2) and mini-modules (21.84 cm2) achieve high efficiencies of 25.38% and 23.22%, respectively. Furthermore, the unencapsulated solar cells deliver remarkable durability under maximum power point (MPP) tracking, maintaining 87% of their initial efficiency over 1000 h. This work provides an important avenue to bridge the gap between lab-scale cells and fab-scale perovskite photovoltaic modules.
CRIS-Team Scopus Importer:2026-01-26